2020
DOI: 10.1021/acs.jmedchem.0c01191
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin and Aclarubicin: Shuffling Anthracycline Glycans for Improved Anticancer Agents

Abstract: Anthracycline anticancer drugs doxorubicin and aclarubicin have been used in the clinic for several decades to treat various cancers. Although closely related structures, their molecular mode of action diverges, which is reflected in their biological activity profile. For a better understanding of the structure–function relationship of these drugs, we synthesized ten doxorubicin/aclarubicin hybrids varying in three distinct features: aglycon, glycan, and amine substitution pattern. We continued to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(67 citation statements)
references
References 52 publications
0
67
0
Order By: Relevance
“…Removal of the anomeric p -methoxyphenol group and installation of the alkynylbenzoate was then achieved as described for donors 9 and 12 to give donor 16 . The three alkynylbenzoate donors 9 , 12 , and 16 were used, alongside daunosamine donor 17 that we previously assembled, 13 in glycosylation reactions toward doxorubicin analogues 2b – 3a / b – 4a / b ( Scheme 2 ). Treatment of a mixture of donor 9 and protected doxorubicinone acceptor 18 ( 22 ) with a catalytic amount of PPh 3 AuNTf 2 in DCM at room temperature led to the formation of anthracycline 19 in 80% yield as an 8:1 α/β-mixture.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Removal of the anomeric p -methoxyphenol group and installation of the alkynylbenzoate was then achieved as described for donors 9 and 12 to give donor 16 . The three alkynylbenzoate donors 9 , 12 , and 16 were used, alongside daunosamine donor 17 that we previously assembled, 13 in glycosylation reactions toward doxorubicin analogues 2b – 3a / b – 4a / b ( Scheme 2 ). Treatment of a mixture of donor 9 and protected doxorubicinone acceptor 18 ( 22 ) with a catalytic amount of PPh 3 AuNTf 2 in DCM at room temperature led to the formation of anthracycline 19 in 80% yield as an 8:1 α/β-mixture.…”
Section: Resultsmentioning
confidence: 99%
“…13,17 In the assembly of doxorubicin/aclarubicin hybrids, we found that the use of an allyloxycarbamate (Alloc) to mask the amino group of the 2,3-dideoxy-3-aminofucose in combination with relatively labile silyl ethers to protect the hydroxyl groups is very effective for the assembly of the anthracycline targets. 13 Thus, alkynylbenzoate donors 9, 12, and 16 were designed and assembled as depicted in Scheme 1. p-Methoxyphenolates 6 and 10 were prepared from precursor 5 18 (a mixture of 33:67 R/S at C3) by treatment with p-methoxyphenol in the presence of catalytic trimethylsilyl trifluoromethanesulfonate (TMSOTf) to give equatorial azide 6 in 50% yield and axial azide 10 in 7%. Deacylation under Zempleń conditions was followed by triethylsilylation of the resultant alcohol.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity is conditioned by the mechanism of cell death induced by anthracyclins, which depends on the cell type and drug concentration [ 10 ]. Consequently, understanding this interplay in anthracyclin/lipidome/cell death might open the possibility to: (i) improve diagnosis by biomarkers of the tumor resistance to anthracyclins [ 11 , 12 ], and (ii) propose novel treatments that may potentiate and/or complement the metabolic transformations caused by anthracyclins to induce cell-death.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity is conditioned by the mechanism of cell death induced by anthracyclins, which depends on the cell type and drug concentration 13 . Consequently, understanding this interplay anthracyclin/lipidome/cell death might open the possibility to: i) improved diagnosis by biomarkers of the tumor resistance to anthracyclins 14,15 , and ii) proposal of novel treatments that may potentiate and/or complement the metabolic transformations caused by anthracyclins to induce cell-death.…”
mentioning
confidence: 99%